Polemika wokół egzemplarza obowiązkowego w latach 1989-2009 - Dąbrowska, Ewa (Biblioteka Uniwersytecka w Poznaniu, 2012)
Artykuł zawiera przegląd literatury dotyczącej egzemplarza obowiązkowego w dwudziestoleciu po 1989 roku. Intensywny rozwój rynku wydawniczego w zmienionych realiach społeczno-gospodarczych oraz pojawienie się nowych środków przekazu sprawiły, że bibliotekarze i wydawcy domagali się zmian w przepisach pochodzących z 1968 roku. Rozbieżność interesów obu stron przejawiała się najbardziej w tym, że podczas gdy biblioteki żądały kontrolowania ruchu wydawniczego, by zwiększyć kompletność przekazywanego egzemplarza obowiązkowego, to wydawcy domagali się znaczącego zmniejszenia liczby uprawnionych bibliotek. Na łamach czasopism bibliotekarskich oraz wydawniczych pojawiały się liczne artykuły prezentujące poglądy, opinie i propozycje bibliotekarzy i wydawców. Można tu wyróżnić kilka etapów dyskusji, od oceny sytuacji po 1989 roku i propozycji zmian przepisów, poprzez uchwalenie ustawy, ocenę nowych przepisów oraz ich funkcjonowania, po kolejne rozmowy i spotkania zmierzające do zmian w ustawie. Artykułowi towarzyszy bibliografia zagadnienia w układzie chronologicznym.

The article provides a review of current literature addressing the issues of the deposit copy scheme within the two decades after 1989. The dynamic development of the publishing market in Poland following the emergence of the new social and economic reality, and the introduction of new media, prompted librarians and publishers to postulate changes in relevant obsolete legal regulations that dated back to 1968. The conflict of, or incompatibility of, interest between the two sections were most apparent in demands submitted by libraries to retain full control over the publishing market in terms of the obligation of publishers to furnish to libraries their complete publishing output according to the deposit copy scheme. On the opposite side of the conflict, publishers demanded the number of eligible deposit copy libraries to be significantly reduced. At the time, library periodicals and publishing journals abounded with articles presenting opinions, views and suggestions put forward by librarians and publishers alike. A number of stages in the discussion can be distinguished: from fact-finding evaluations produced soon after 1989 and proposals referring to changes in regulations with regard to passing an act in the lower house of the Parliament (the Polish Sejm), appraisals of new legal regulations in the light of their actual operation, to a new debate on amendments and changes in the Act. The article is complemented with an extensive bibliography in chronological order.
A polemic about the deposit copy scheme in the years 1989-2009
Keywords: egzemplarz obowiązkowy; deposit copy; gromadzenie zbiorów; collection acquisition; prawo; law; rynek wydawniczy; publishing market; Biblioteka Narodowa; National Library; Biblioteka Jagiellońska; Jagiellonian Library; biblioteki uniwersyteckie; University libraries